Effect of Cooperative Membership on Production of Plantain Farmers in Ijebu North Local Government Area, Ogun State, Nigeria - Akerele, Ezekiel Olaoluwa; Okewale, Joel Adeniyi; Ariyo, Oludayo Olajide; Ogunyemi, C.S. (Acta Universitatis Danubius. Œconomica, 2024)
The study aimed to evaluate the impact of cooperative membership on the productivity of plantain farmers in Ijebu North Local Government Area, Ogun State, Nigeria. It specifically examines the socio-economic characteristics of these farmers, the influence of cooperative membership on their production, access to resources, and the cost-return structure of their farming activities. Primary data were collected for this study using Questionnaire. The study employs both descriptive and inferential statistical methods. Data collected were analyzed using Descriptive statistics, Multiple regression analysis, Logistic regression and Budgetary analysis. The results revealed that cooperative membership significantly influences plantain production, with an R-squared value of 0.441, indicating that 44.1% of the variation in plantain production is explained by the independent variables. Age (β = 0.380, p < 0.001), access to extension services (β = 0.154, p = 0.276), and farm size (β = 0.063, p = 0.399) positively impact production, while gender (β = -0.274, p = 0.002) and access to information (β = - 0.258, p = 0.035) negatively influence production. Among the farmers (36.0%) are male, and 64.0% are female. In terms of access to resources, logistic regression results show that cooperative membership increases the probability of accessing land (β = 0.400, p < 0.05), inputs (β = 0.330, p < 0.05), and credit (β = 0.290, p < 0.05). The cost-return analysis indicates that the average return on investment (ROI) for plantain farmers is 1.45, meaning that for every Naira invested, farmers earn N1.45 in return. Based on these findings, it is recommended that agricultural cooperatives enhance their support systems, particularly in providing easier access to resources and addressing the capital needs of farmers. The study concludes that cooperative membership can be a valuable tool for improving the productivity and sustainability of plantain farming in the study area, provided that the identified challenges are adequately addressed.